Síntese e Caracterização de Biodiesel de Sebo Bovino e de sua Mistura B10 - Silva, Antônio Alex de Lima; Santos, Anne G. Dias; Di Souza, Luiz; Caldeira, Vinicius P. da Silva; Luz Junior, Geraldo Eduardo; Araújo, Antônio Souza (Orbital: The Electronic Journal of Chemistry, 2015)
Biodiesel has become an alternative to mineral diesel; it already has been in 7% biodiesel to diesel. The intention of the Brazilian government to increase the biodiesel content in the mixture to 10% which will promote an increase in demand for raw materials for the production of biodiesel. Among them is the beef tallow which is presented as one of the cheapest raw materials among the available ones. Associated with this increase in production has been the need to improve the processes of synthesis and analyze their properties as oxidative stability (OS) in mixtures with mineral diesel. Based on this, this study aimed to analyze the physicochemical properties and oxidative stability tallow biodiesel B10 and its beef mixture. In the present work, beef tallow biodiesel was synthesized through methylic rout and was mixture to mineral diesel type B (10 wt %) without anything additives. Physic-chemical properties of biodiesel samples and that mixture were determinate, indicating that both samples are agreement with Brazilian Specifications, and the mixture has showed around 10% less sulfur than diesel. Furthermore, oxidative stability of beef tallow biodiesel is higher than at stipulated in norm. DOI: http://dx.doi.org/10.17807/orbital.v7i1.680